Beltrami-Meusnier formulas of generalized semi ruled surfaces in semi Euclidean space - AKYIG١IT MAHMUT; ERSOY, SOLEY; TOSUN, MURAT (Kuwait Journal of Science, 2014)
In this paper, we study the sectional curvatures of the generalized semi ruled surfaces in semi Euclidean space The first fundamental form and the metric coefficients of the generalized semi ruled surfaces are calculated and in these regards, Riemannian-Christoffel curvatures are obtained by the help of Christoffel Symbols. So, the curvatures of arbitrary non-degenerate tangential sections of the generalized semi ruled surface are investigated. In addition to this, the relations between the sectional curvatures are obtained. These are called semi Euclidean Beltrami-Meusnier formulas.